Design and Analysis of Injection Molds for Plastic Components for Biomedical Applications - Madhukumar Krishnappa; Santhosh Nagaraja; Nataraja Munegowda; Muhammad Imam Ammarullah (Engineering Reports)
ABSTRACT The injection molding process primarily involves a systematic sequence that converts plastic pellets into molded components. This method produces identical parts by repeatedly melting resin pellets or powder and injecting the molten polymer into a hollow mold cavity under high pressure. The injection molding technique presents challenges for manufacturers and researchers striving to create cost‐efficient products that meet stringent criteria. This research delves into the holistic process of designing, analyzing, and manufacturing injection molds for plastic components used in biomedical applications, with a focus on cost‐effectiveness while overcoming common hurdles to achieving high‐quality parts. Polypropylene talc filled (PPTF) is selected for its enhanced stiffness, making it suitable for applications demanding dimensional stability. Moldflow simulation helps identify potential problems such as uneven flow, weld line issues, and air traps. Based on these insights, mold design is optimized through strategic gate placement, weld line management, elimination of gas traps, pressure drop equalization, and stress reduction. Implementing these optimized parameters in the manufacturing phase leads to improved part quality, characterized by fewer defects and better dimensional accuracy. Furthermore, this research aids in minimizing production costs by decreasing rejections and rework. This multifaceted approach not only refines the process but also supports the efficient and cost‐effective production of high‐quality plastic components for biomedical applications.